An epidemiological survey of cataract among adults aged 50 years and above in rural, Shaanxi Province - Fang Tian (Guoji Yanke Zazhi, 2014)
AIM: To investigate prevalence of cataract and status surgery of cataract among adults aged 50 years and above in rural, Shaanxi Province, and to evaluate the rate of blindness caused by cataracts and postoperative effects. METHODS: Cluster sampling was used in randomly selection in Shaanxi Province from Jan. to Dec. in 2011, among the 3494 individuals from Liuba county, Huangling county, Lantian county and Baqiao district, 2124 aged 50 years and above received questionnaire survey and eye examination in the study. WHO diagnostic criteria and cataracts diagnostic criteria were used in the evaluation. RESULTS: Of 1912 participated the eye survey and response rate was 90%, the prevalence of cataracts was 36.66%, and the prevalence of cataracts among adults aged 50 years and above was 15.80%, the prevalence of cataracts among adults aged 70 years and above was 68.71%. The prevalence of age-related cataracts increased obviously with aging(P<0.01). The prevalence of bilateral blindness and low vision caused by cataract was 1.99% and 7.17%, respectively. The rate of bilateral blindness and low vision and monocular blindness and low vision was 0.51%, 0.63%, 1.90%, 2.53% respectively, increasing to 4.55%, 5.35%, 16.44%, and 18.81% in those aged 70 years and above. There was statistically significant difference in cataract blindness of different age groups and incidence of low vision, increased obviously with aging(P<0.01). Among 86 eyes with cataract surgery, 58 eyes were given ECCE, and 23 eyes were given PHACO, and 5 eyes were given ICCE. The corrected vision after cataract surgery ≥0.3 occupied 69.09%, 23.64%, 7.27% in ECCE, PHACO and ICCE respectively. The rate of off-disability and off-blindness was 63.95%, 91.86%, respectively. CONCLUSION: Cataract blindness is a serious public health problem in rural, Shaanxi Province. Prevention of blindness in Shaanxi Province has made some achievements, and the prevalence of cataract and visual impairment have decreased to some extent. PHACO has been carried out in rural areas, however, the penetration and surgical techniques of PHACO should be further improved.